Spirituality and Psychological Well-Being of Students Affected by Pandemic Covid-19 in Banda Aceh - Syahputri, Nadia; Safrilsyah, Safrilsyah; Fatmawati, Fatmawati (Journal of Islamic and Contemporary Psychology, 2023)
Spirituality is an attitude that reflects the spirit of religiosity and religion. Spirituality includes many special things such as admiration, gratitude, feelings of love, compassion, and the desire to be close to God. One of the factors that influence spirituality is psychological well-being. This study aims to determine the relationship between spirituality and psychological well-being of UIN Ar-Raniry students. This study uses a quantitative approach with the correlational method. The Sampling was carried out using a proportionate stritified random sampling technique of 342 students at UIN Arraniry, Banda Aceh. Data was collected using two questionnaires, (1)Spirituality Scale which was made based on aspects of Underwood (2006) with a reliability result of α = 0.929, and (2) Psychological Well-Being Scale which was made based on aspects of Ryff (1989) ) with a reliability result of α = 0.927. The data analysis used in this study is the Spearman Rank correlation which shows that there is a relationship between spirituality and psychological well-being, with an r2 value of 0.577, with p = 0.000 (<0.05), which indicates that there is a very significant positive relationship between spirituality with psychological well-being in UIN Ar-Raniry Banda Aceh students affected by Covid-19